If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9+3n=2n+1
We move all terms to the left:
-9+3n-(2n+1)=0
We get rid of parentheses
3n-2n-1-9=0
We add all the numbers together, and all the variables
n-10=0
We move all terms containing n to the left, all other terms to the right
n=10
| -10-9y=72 | | -2.8x=16.8 | | 8+6r=4r | | -x=-3(8+1x) | | (z-13)+180+(z+10)=360 | | -x=-3(8+1x | | 10h-7=4h-7-h | | 8(4-b)+3(-7-b)=55 | | x•3=-30 | | 31=9x-5 | | -n+2=7* | | 30x=2+3 | | 11r+13=57 | | 10+10g-10=9g-7 | | 9-4x=3+x2 | | -5(-5x+2)-4x=5(x-3)-7 | | 15.6=7.8x | | (4x+13)+(6x+2)+(180-(14x-13))=180 | | 5+x/6=-6 | | 27=9*3+8y | | -q+1=2q+10 | | 3(b+1)+1=4b | | -(p+3/5)=-4 | | x=(2^23)*(2^23) | | 8a+15=-1 | | 10+2r-8=10+4r | | d−35=50 | | 7(w-84)=63 | | 60=8x+44 | | 68=k+15 | | (-4x+43)=(-6x-13) | | -5.5x=-22 |